The Impact of Tax Policy on Investment Climate in Ukraine - Zhamoida, O.A.; Arnoldova, A.A. (Економічний вісник Донбасу, 2013)
This article examines the impact of tax policy on the investment climate of Ukraine in recent years. Also it analyzes the positive effects of the adoption of the Tax Code and its amendments in 2011 - 2013, and therefore, changes in the investment attractiveness of Ukraine. У статті було розглянуто вплив податкової політики на інвестиційний клімат України за останні роки. Також було проаналізовано позитивні наслідки прийняття Податкового кодексу й поправок до нього у 2011 - 2013 роках, і відповідно зміни в інвестиційній привабливості України. В статье было рассмотрено влияние налоговой политики на инвестиционный климат Украины за последние годы. Также были проанализированы положительные последствия принятия Налогового кодекса и поправок к нему в 2011 - 2013 годах, и соответственно изменения в инвестиционной привлекательности Украины.